Obtain of sulfuric acid at the electrochemical processing of eluates - Gomelya, M.; Trus, I.; Grabitchenko, V.; Petrichenko, A. (Видавництво Львівської політехніки, 2013)
It is shown that by the electrolysis of eluates it is possible to obtain sulfuric acid solutions. It was found that in process of electrolysis sulfuric acid concentration can be increased up to 44% at very satisfactory values for the current output. It was found that with increasing current density the rate of electrochemical concentration of sulfuric acid significantly increases at the anode with decreasing acid current efficiency.
Keywords: sulfuric acid; anion exchange membrane; electrodialysis; electrolysis; reverse osmosis; ion exchange; concentration; desalting; processing of eluates